2001
DOI: 10.1159/000048731
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Regulates Terminal Schwann Cell Number and Junctional Size during Developmental Synapse Elimination

Abstract: Previous work has shown that exposure to exogenous testosterone during synapse elimination permanently stabilizes synapses that would normally be lost in the androgen-sensitive levator ani (LA) muscle, indicating that testosterone is a potent stabilizing factor for developing LA synapses. Terminal Schwann cells (TSCs), which cap the neuromuscular junction, have also been implicated in the control of synaptic stability and may play a decisive role in the selective stabilization of synapses during synapse elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Estradiol, progesterone and testosterone enhance Schwann cell proliferation (Jordan and Williams, 2001;Jung-Testas et al, 1993;Lubischer and Bebinger, 1999;Svenningsen and Kanje, 1999) and the proliferation of oligodendrocyte precursors (Ghoumari et al, 2005;Marin-Husstege et al, 2004). In contrast, glucocorticoids decrease proliferation of oligodendrocyte precursors (Alonso, 2000).…”
Section: Glial Cell Responses To Steroid Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol, progesterone and testosterone enhance Schwann cell proliferation (Jordan and Williams, 2001;Jung-Testas et al, 1993;Lubischer and Bebinger, 1999;Svenningsen and Kanje, 1999) and the proliferation of oligodendrocyte precursors (Ghoumari et al, 2005;Marin-Husstege et al, 2004). In contrast, glucocorticoids decrease proliferation of oligodendrocyte precursors (Alonso, 2000).…”
Section: Glial Cell Responses To Steroid Actionsmentioning
confidence: 99%
“…Finally, it should be considered that although steroids may act directly on glial cells in vitro, the final response of glial cells to steroids in vivo is probably influenced by interactions with neurons. For instance, neuronal signals are required for estrogen-mediated induction of progesterone receptor in cultured rat Schwann cells and androgen-receptors expressing neurons probably mediate the effect of androgens on Schwann cell proliferation (Jordan and Williams, 2001) and on the expression of glycoprotein zero (P0) in the sciatic nerve (Magnaghi et al, 1999). Some effects of progesterone on Schwann cells may also be mediated by neuronal progesterone receptors (Chan et al, 2000).…”
Section: Glial Cell Responses To Steroid Actionsmentioning
confidence: 99%
“…It has been shown that there are 3-5 PSC somata in both frog and mammalian mature NMJs, and that the number of PSCs is correlated with the endplate size (Herrera et al 1990;Love and Thompson 1998;Lubischer and Bebinger 1999;Jordan and Williams 2001). It is not clear why PSCs are nonmyelinating even though they can be labeled with antibodies to myelinating glial markers, such as protein zero (P 0 ), myelin-associated glycoprotein (MAG), galactocerebroside, and 2 0 , 3 0 -cyclic nucleotide 3 0 -phosphodiesterase .…”
mentioning
confidence: 99%
“…Schwann cells are present at NMJs soon after initial nerve-muscle contact (Kelly and Zacks 1969;Herrera and others 2000), and the number of these PSCs increases during the first two postnatal weeks, before the phase of rapid synapse growth (Love and Thompson 1998). Moreover, the number of PSCs per endplate is matched to endplate size: their number increases as endplates enlarge and decreases if endplates shrink (Lubischer and Bebinger 1999;Jordan and Williams 2001). More direct evidence of the importance of PSCs comes from knockout mice that lack Schwann cells.…”
Section: Roles Of Pscs In Synaptogenesismentioning
confidence: 99%